Policy, institutional, and expenditure review of bottom-up approach disaster risk reduction and management - Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2021)
Republic Act (RA) 10121, or the Philippine Disaster Risk Reduction Management (DRRM) Act of 2010, has led to the passing of complementary legislation and functional policy, bureaucratic and institutional augmentations and directed government budgeting and spending. Key thematic mandates were given to national government agencies while the bulk of policy implementation, institutional grounding, and resource allocation related to DRRM were devolved to local government units, granting them fiscal and administrative authority. The policy also facilitated opportunities and invitations for participatory bottom-up approaches. However, gaps, such as on structured reporting and appraisal of DRRM budget and spending and bottom-up participation, also existed. Using mixed-methods, qualitative inputs from key informant interviews and focus group discussions, as well as quantitative data encoded from the 2015-2019 Full Disclosure Policy Portal (FDPP) of the Department of Interior and Local Government were used to provide evidence and establish narratives on how policy, institutional structures, and public investment contributed to LGU functioning and community preparedness and participation. It was found out that there were sub-optimal allocations despite the abundance of fiscal resource in both the national and subnational governments regardless of location and income levels. The highest utilization rate for which were identified in disadvantaged regions (ARMM, Region 3, Region 9). As the predominant arrangement across the DRRM landscape was still top-down, communities have much to lose due to their weak visibility in participatory governance and nearly invisible decisionmaking powers in the formulation of plans and approval of programs. While community resilience was stated to be the core of RA 10121, institutional structures still need to strengthen their enabling mechanisms for representation and stakeholder participation. Expenditures should explicitly support more community-led initiatives as well as proposals from sectoral committees, and barangay councils. Monitoring and evaluation strategies should also capture and track DRRM funds, goods and services, across agencies, fund sources, and varying enabling conditions accurately.
Keywords: 330; disasters; public investment; policy framework; institutional structures; community; bottom-up approach; participatory